Pengaruh Iklim Keselamatan dan Persepsi Keselamatan Pengawas terhadap Kinerja Keselamatan: (Studi Kasus pada PT PLN (Persero) ULPLTD Kolaka) - Suryadil Badwin; Niar Astaginy; Andry Stepahnie Titing (Jurnal Mahasiswa Kreatif, 2023)
This Research Aims To Know: (1) The Effect of Safety Climate on Safety Performance at PT PLN (Persero) ULPLTD Kolaka. (2) The Effect of Perceived Supervisor Safety on Safety Performance at PT PLN (Persero) ULPLTD Kolaka. This study used a quantitative method approach, collecting data in this study using observation, documentation and questionnaires. The population in this study are employees who work at PT PLN (Persero) ULPLTD Kolaka. While the sample in this study amounted to 51 people. Testing research instruments using validity and reliability tests with SPSS 25.0. The data analysis technique used in this study is to test the measurement model (outer model) and test the structural model (inner model) with smart PLS 4.0. Based on the research results, it is known that there is a positive and significant influence between the safety climate variables on safety performance. What is shown is the statistical value of 2.741, the original sample value is 0.548 and the P-value is 0.006. for the perceived supervisor safety variable has a positive and insignificant effect on safety performance showing a statistical value of 0.944, the original sample value is 0.191 and the P-value is 0.345.